Assessment of Malondialdehyde and Soluble α-Klotho Serum Levels in Iraqi Acromegaly Patients - Hameed, Areej Sh.; Abed, Baydaa A.; Mahdi, Osama A.; Rahmah, Abbas M. (Iraqi Journal of Science, 2024)
Acromegaly has been associated with several metabolic health conditions that can increase risks of death and illness. These include heart disease, diabetes, and problems with how the body regulates insulin levels. Multiple studies have found that people living with acromegaly are two to four times more likely to pass away than others of the same age and sex in the general population. Research also suggests a link between acromegaly and higher levels of malondialdehyde (MDA) in the body. MDA is a byproduct formed during natural processes like prostaglandin and lipid peroxidation production that is able to damage genes and has been connected to cancer development. The transmembrane protein known as soluble a-Klotho (SAKL) is named after a Greek deity. Numerous age-related illnesses, including osteoporosis, pulmonary emphysema, skin shrinkage, and atherosclerosis, have been shown to affect α -Klotho-deficient mice. Sixty subjects (30 males and 30 female) Mean ± SD was (53.2±10.5). diagnosed with acromegaly and 30 (15 males and 15 female) healthy group Mean ±SD was (52.1±13.5). the age range between (30-60) years. Laboratory measurement including serum Insulin like growth factor-1 (IGF-1), Growth hormone (GH) Fasting serum glucose (FSG), lipid profile (Total Cholesterol (TC), Triglyceride (TG), High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), Very Low-Density Lipoprotein (VLDL)), Soluble a-Klotho (SAKL), Malondialdehyde (MDA). The results showed significantly higher P ≤ 0.01 IGF1, GH, FSG, TC, TG, LDL, VLDL, SAKL, and MDA levels in patients’ group Compared to healthy group. In patients’ group SAKL had a positive significant correlation with HDL, and negative significant correlation (P ˂ 0.01) with LDL, on the other hand, there was a substantial relationship P ˂ 0.01 between (TC, TG, and LDL) with MDA. The research findings suggest that levels of SAKL and MDA are increased in patients with acromegaly, potentially serving as novel biomarkers for assessing active acromegaly. The measurement of SAKL and MDA could prove valuable, particularly in cases where GH and IGF-I results are inconclusive or conflicting